Development and validation of InnoQuant® HY, a system for quantitation and quality assessment of total human and male DNA using high copy targets. (July 2017) - Loftus, Andrew; Murphy, Gina; Brown, Hiromi; Montgomery, Anne; Tabak, Jonathan; Baus, James; Carroll, Marion; Green, André; Sikka, Suresh; Sinha, Sudhir
Highlights: Developmental validation of a qPCR multiplex assay, InnoQuant® HY. Provides an assessment of sample quality (Degradation Index) and total and male DNA quantity. Four targets are included: autosomal 80 bp, autosomal 207 bp, male 79 bp, and a 172 bp synthetic IPC. Highly sensitive, reproducible, and valuable results for making informative decisions during DNA analysis process. InnoQuant® HY results correlate well with downstream autosomal and Y STR DNA typing methods. Abstract: The development and validation of InnoQuant ® HY, a real-time PCR system containing four DNA targets—two RE autosomal targets of different sizes, male specific targets, and an internal positive control target—are described herein. The ratio of the two autosomal targets provides a Degradation Index, or a quantitative value of a sample's degradation state. The male specific targets are multi-copy targets located on the Y chromosome, which provides information about a sample's male DNA composition. The experimental results demonstrate InnoQuant HY as a robust qPCR method producing accurate DNA quantitation results even at low dynamic ranges, with reproducibility among population groups. The system is human specific with low level higher primate cross reactivity and is able to consistently and reproducibly detect sub-picogram concentrations of human and human male DNA. The use of high copy number Alu and SVA (>1000 copies per genome) retrotransposable elements as the two autosomal targets significantly enhances both sensitivity and reproducibility of determination of DNA quantitation as well as DNA degradation in forensic samples. The inclusion of a sensitive multi-copy Y-chromosome specific target provides accurate quantitation of DNA from a male in challenging male-female mixtures (i.e. sexual assault samples). Even in the presence of a large excess of DNA from a female, accurate quantitation was achieved with a male to female ratio of 1:128, 000. Population database studies reveal an average Short/Y target ratio of the quantification values across all four populations tested was 1.124 ± 0.282, exhibiting the system's reproducibility across multiple populations. The results from InnoQuant HY provide a tool equipping a forensic analyst with crucial data about a sample's DNA quantitation, male:female ratio, degradation state, and the presence or absence of PCR inhibitors. With the information gained from the InnoQuant HY kit, a more streamlined and efficient workflow can be created that minimizes unnecessary sample processing and retesting while maximizing recovery of probative DNA profiles from challenging biological evidence.